Effect of Mind-regulating Brain-developing Moxibustion on Cognitive Function and Sleep Quality in Patients with Mild Cognitive Impairment - Xinyan JIA; Tingting TAN; Dan WANG; Xu YUAN; Yazi MEI; Shangjie CHEN (康复学报)
Objective:To explore the effect of mind-regulating brain-developing moxibustion on cognitive function and sleep quality in patients with mild cognitive impairment (MCI).Methods:A total of 60 MCI patients were randomly assigned to the moxibustion group and control group, 30 cases in each group. The moxibustion group received moxibustion treatment of mind-regulating brain-developing, once a day, six times a week, four weeks as a course of treatment for a total of two courses of treatment; While the control group did not accept any intervention. Before and after treatment, the cognitive function of the two groups was evaluated by Montreal Cognitive Assessment Scale (MoCA), Webster's number sign test and Webster's digital breadth test, and the quality of sleep was evaluated by the Epworth Sleepiness Scale (ESS), Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index Scale (PSQI).Results:After two courses of treatment, the score of MoCA, number sign and digital breadth scale in moxibustion group were significantly higher than those before treatment (P<0.05), and the difference was also statistically significant between the two groups after treatment (P<0.05). The scores of ESS, ISI and PSQI in moxibustion group after two courses of treatment were significantly lower than those before treatment (P<0.05). The difference between the two groups after treatment was also significant (P<0.05). In the cognitive field, the scores of attention and delayed memory in the moxibustion group were significantly higher than those before treatment (P<0.05), and the scores of visual space and executive and delayed memory in the control group were significantly lower than those before treatment (P<0.05). There were significant differences between the two groups in the scores of visual space and executive and delayed memory after treatment (P<0.05).Conclusion:Mind-regulating brain-developing moxibustion can improve the cognitive function and sleep quality of MCI patients.